2022
DOI: 10.3390/arm90040044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Serum Adrenomedullin in Patients with Ventilator Associated Pneumonia

Abstract: Objective: Ventilator associated pneumonia is a common type of sepsis that occurs to about 9–27% of all mechanically ventilated patients and 20–50% of them develop septic shock. Several clinical, laboratory, and radiological methods have been used for diagnosing VAP. Adrenomedullin (ADM) has been found to be elevated in the plasma of septic patients. The study aim was to explore the prognostic role of ADM in the VAP patients. Design: A prospective observational study. Setting: Intensive Care Department of Alex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…154 A recent study reported that serum AM levels are also a promising predictive marker in the assessment of ventilator-associated pneumonia diagnosis. 155 Of note, it has long been demonstrated that AM also has an antimicrobial role, participating in the prevention of local infection acting synergistically with the immune response (Figure 2). 156 Interestingly, antimicrobial effects of AM seem to be independent from its classical signaling pathway.…”
Section: Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…154 A recent study reported that serum AM levels are also a promising predictive marker in the assessment of ventilator-associated pneumonia diagnosis. 155 Of note, it has long been demonstrated that AM also has an antimicrobial role, participating in the prevention of local infection acting synergistically with the immune response (Figure 2). 156 Interestingly, antimicrobial effects of AM seem to be independent from its classical signaling pathway.…”
Section: Pneumoniamentioning
confidence: 99%
“…154 A recent study reported that serum AM levels are also a promising predictive marker in the assessment of ventilator-associated pneumonia diagnosis. 155…”
Section: Cardiovascular Correlates In Other Prevalent Diseasesmentioning
confidence: 99%
“…Its expression is up-regulated in response to various stimuli such as hypoxia, inflammation, and mechanical stress [ 19 , 21 ]. Adm has been implicated in several pathological conditions, including cardiovascular diseases [ 20 , 22 , 23 , 24 , 25 ], pulmonary disorders [ 26 , 27 , 28 , 29 , 30 ], gastrointestinal disorders [ 31 , 32 ], sepsis [ 33 , 34 , 35 , 36 ], cancer [ 20 , 32 , 37 , 38 ], and disorders associated with pregnancy [ 39 , 40 , 41 , 42 ]. Since Adm is highly enriched in the lungs, its expression is influenced by inflammation, and the peptide plays a vital role in maintaining endothelial cell homeostasis [ 43 , 44 , 45 ]; Adm may play a pathogenic role in inflammatory lung disorders such as BPD.…”
Section: Introductionmentioning
confidence: 99%